Correction: Glioblastoma induces CAF-like astrocyte activation via the AKT/mTOR–SERPINH1/COL5A1 axis - Jingxian Zhang; Yajia Chen; Hongwu Xu (Biomolecules & Biomedicine)
Correction to: Glioblastoma induces CAF-like astrocyte activation via the AKT/mTOR–SERPINH1/COL5A1 axis